1964
DOI: 10.1007/bf02663965
|View full text |Cite
|
Sign up to set email alerts
|

Straight‐chain alkylbenzenes: Structure and performance property relations

Abstract: An intensive study of the mass spectral characteristics of straight‐chain alkylbenzenes has been made in conjuction with their ultimate performance as sulfonates in heavy duty formulations. Two variables of the alkylates, carbon‐chain length distribution (which fixes the mean mol wt) and phenyl position on the chain, have been successfully related to the observed dishwashing performances. Formulas are given which allow accurately predicting this performance criteria. The important role of phenyl position is il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The popularity of ABS stems from their cost-effectiveness, biodegradibilty, and the fact that the interfacial tension between oil and water can be lowered to extremely low values on the order of 10 –3 mN/m . The effectiveness of ABS as detergents has been correlated to the molecular weight of the surfactants as well as the position of the benzene ring along the alkyl chain. It was found that a surfactant produces a minimum interfacial tension for a particular alkane, and there was an optimal position for the attachment of the benzene ring to the alkyl chain where the effect on the interfacial properties was greatest, depending on the alkane used.…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of ABS stems from their cost-effectiveness, biodegradibilty, and the fact that the interfacial tension between oil and water can be lowered to extremely low values on the order of 10 –3 mN/m . The effectiveness of ABS as detergents has been correlated to the molecular weight of the surfactants as well as the position of the benzene ring along the alkyl chain. It was found that a surfactant produces a minimum interfacial tension for a particular alkane, and there was an optimal position for the attachment of the benzene ring to the alkyl chain where the effect on the interfacial properties was greatest, depending on the alkane used.…”
Section: Introductionmentioning
confidence: 99%
“…There are widespread opinions in the detergent industry about the comparative performance and formulation characteristics of high versus low 2-phenyl LAS (2). Differences which were noticed were attributed to the phenyl isomer distribution and in some cases this has led to misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…of benzene with olefins in the presence of Friedel-Crafts catalysts. Studies on the solubility, foam stability, and surface-active properties of these products have shown that the length of their alkyl chain and the position of the phenyl group on it are important factors in determining their performance characteristics (Anstett et al, 1966;Rubinfeld et al, 1964Rubinfeld et al, , 1965. Certain constant synergistic effects have also been observed for various combinations of phenylalkanes (Sweeny and Olson, 1964).…”
mentioning
confidence: 99%